PENGARUH KOMPETENSI, ETIKA, PENGALAMAN AUDITOR TERHADAP KUALITAS AUDIT - Brishana Abigael Sinurat; Hisar Pangaribuan (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
The purpose of this study was to ascertain the influence of auditor expertise, ethics, and experience on audit quality. 150 accountants from three separate firms made up the sample for this study. Questionnaires are distributed to gather the data. Direct sampling was employed for the sampling procedure, and multiple linear analysis was performed for data processing with the SPSS Windows version 25 software. The findings of this study suggest that the quality of audit results can be somewhat influenced by the expertise, ethics, and experience of auditors.